Factores que intervinieron en la reprobación de la asignatura matemáticas en la educación básica superior del período lectivo 2014-2015 de la Unidad Educativa Eloy Alfaro en la ciudad de Quevedo - Barros, Wilson (2019)
The research was based on determining the factors that intervened in the failure of the subject in the General Basic Education of the Eloy Alfaro Educational Unit in the city of Quevedo. It was also investigated by means of five-choice Likert type questionnaires that allowed obtaining information about the influence on the learning of mathematics, such as the student's mathematical attitudes, teacher attitudes and parental attitudes that could influence learning; the variables include the proper context, family and school in the use and learning of mathematics. The results reflect that the quality of the teaching task is related to the integral development, because the challenge to get the students to develop thinking skills. Most students show positive attitudes towards the subject. In the behavior of parents aims to influence directly therefore it is necessary to promote family environment that encourages pleasure in academic tasks, especially in the subject of mathematics. The control exercised by parents over students has an impact on academic performance